Construction and Empirical Study of an Evaluation System for Automotive Touch Interaction Performance in Extreme Temperature Environments - Wang, Shimeng; Zhang, Qipeng; Zhao, Meng; Tian, Zhe (Scientific Journal of Technology, 2025)
To address the issues of easy performance degradation of automotive touch interaction systems in extreme temperature environments and the lack of targeted evaluation in existing systems, this study develops an evaluation system for automotive touch interaction performance in extreme temperature environments. First, through literature analysis, the composition and working principles of automotive touch interaction systems are sorted out, and combined with case studies, the influence mechanisms of extreme temperatures on the hardware materials, electronic components, and software stability of touch systems are analyzed. Second, aiming at the defects of incomplete index coverage and imperfect methods in existing evaluation systems for extreme temperature scenarios, experience from temperature evaluation in the electronic equipment and aerospace fields is drawn upon. Twelve core evaluation indicators are selected and optimized from three dimensions: hardware performance, software stability, and human-computer interaction experience. Test methods and standardized procedures for high temperature (50-85℃), low temperature (-40 to -10℃), and temperature shock (-40℃→85℃ cycle) are designed, and a five-level performance evaluation standard is formulated. Finally, empirical tests are conducted on three different vehicle models. Variance analysis and correlation analysis are used to verify the validity of the indicators. The results show that this system can accurately quantify the variation rules of key performance parameters such as touch response delay and recognition accuracy under extreme temperatures, with the recognition error rate reduced by 18.3% compared with traditional evaluation methods. The constructed evaluation system fills the technical gap in the evaluation of automotive touch interaction performance under extreme temperature scenarios and provides standardized technical support for the temperature-resistant design optimization and performance verification of automotive touch systems.